EEO and the promotion of women in the secondary education sector : legislating for change : a thesis submitted in partial fulfulment of the requirements for the degree of Master of Educational Administration at Massey University - Spence, Gail P (Massey University, 1995)
This thesis explores the ways in which two co-educational secondary schools in Aotearoa-New Zealand responded to the requirement under the State Sector Amendment Act (1989) to develop and implement an equal employment opportunities (EEO) policy that would enable women to move into senior administrative positions. The period covered is the May 1989-July 1992 term of office of the new Boards of Trustees established under the Tomorrow's Schools reforms. The study presents, examines and theorises the social, political and educational contexts in which the policy evolved. In the attempt to locate significant sites of struggle in the EEO debate and assess their implications for the promotion of women teachers to senior positions in educational administration, a political model of policy is employed based on a theory of discourse inherent in feminist post-structuralist perspectives. The focus of the research study is on the EEO policy implementation process as it was occuring in two historically specific settings. That process consisted of ongoing struggles between contenders of rival and competing interests. These interests construed in and through discourses specific identities, roles and attributes which were seen to compose our subjectivities, shape decisions and affect appointment practices and outcomes. Interviews were held during 1992 with eighteen personnel in a range of teaching and administrative positions in the two schools. The transcripts were then used to produce a view of the discursive constructions within the field of EEO and place these alongside existing written reports and records, official policy documents and literature analyses. The study found evidence of an internal struggle between competing models of EEO. As well, EEO was discursively constructed as a unified concept through a discourse which competed for allegiances against other discourses within the power networks. Specifically, attention was paid to mapping the links between "teachers, gender and careers" (Acker, 1989) and to the complex positioning of multiple discourses within merit as an ideological construct. This thesis opens up to scrutiny particular discursive constructions and uses, and argues the need to recognise and assume responsibility for each of our own discursive practices and positionings. This necessitates working towards coherence between the discourses of EEO and the discourses of secondary education sector employers' personal and broader professional lives.
Keywords: Women in education; New Zealand; High School Teachers; Selection and employment